Effect of amendment with compost of pear pomace on forage production of Setaria italica (L.) P. Beauv. (Semiárida, 2019)
The juicing industries generate large volumes of pomace, being composting an ecological alternative to recycle this residual organic matter. The objective of this work was to evaluate the production of forage in the cultivation of "Hungarian millet" cv. "Colorada Gigante" in response to the addition of variable doses of pear pomace compost to a sodium saline soil. An organic amendment of 0; 30; 60; and 90 t.ha–1 (dry weight content 79%) was used, evaluating plant development through plant height (AP) and dry weight (PS) at the start of panning of the crop. The results obtained showed that only the application of 90 t.ha–1 caused a significant increase of AP and PS, also observing a linear correlation between plant height and dry weight (R2 = 0.8). The observed effects allow to affirm that with the addition of this organic amendment it is possible to increase its production in suboptimal conditions related to the type of soil and date of planting.
Keywords: biodegraded agroindustrial wastes; hungarian millet; organic amendment; pastures; saline soils